The Computational Unified Field Theory (CUFT): Can Human Consciousness Affect the Cosmos? (Global Journal of Science Frontier Research, 2018)
Twenty-First Century's Theoretical Physics is undergoing a major "Paradigmatic-Shift", i.e., from the old "Material-Causal" Paradigm of Relativity Theory (RT) and Quantum Mechanics (QM) to the new 'A-Causal Computation' Paradigm associated with the 'Computational Unified Field Theory' (CUFT). Based on initial empirical validation of the CUFT as more valid than RT and QM through its 'differentialcritical' prediction associated with the "Proton-Radius Puzzle" (Bernauer & Pohl, 2014), the current article sets to test a hypothetical possible theoretical implication of this CUFT, wherein Individual Human Consciousness may potentially affect certain physical effects in the physical universe; This intriguing new prediction of the CUFT stems from its earlier discovered theoretical postulate of the "Individual Human Consciousness Expansive Spectrum Hypothesis" (IHCESH).